2020
DOI: 10.7575/aiac.ijels.v.8n.1p.48
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Multicultural Education Research: A Five-Year Content Analysis of Turkish and ERIC Databases

Abstract: This study aims to determine trends in research on multicultural education in Turkish and Eric databases, to compare and to discuss them. Within the scope of the study, research on multicultural education in the International Education Resources Information Center (ERIC) and ULAKBİM TR Index (Turkey National Academic Network and Information Center) databases were included. In the study, 308 articles reached in ERIC database and 60 articles in ULAKBİM database were analyzed using content analysis. As a result o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Another factor influential in intensifying quality social contact in order to lessen xenophobic attitudes towards migrant students is multicultural education. Multicultural education helps students develop positive attitudes towards individuals from different cultural groups, reduces discriminatory attitudes and raises tolerance among groups (Köşker & Erdoğan, 2020). In an educational system based on a single culture that denies existent diversity in social structure, individuals may develop negative and marginalizing attitudes towards different cultural groups (Parekh, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Another factor influential in intensifying quality social contact in order to lessen xenophobic attitudes towards migrant students is multicultural education. Multicultural education helps students develop positive attitudes towards individuals from different cultural groups, reduces discriminatory attitudes and raises tolerance among groups (Köşker & Erdoğan, 2020). In an educational system based on a single culture that denies existent diversity in social structure, individuals may develop negative and marginalizing attitudes towards different cultural groups (Parekh, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…, who analyzed the studies on multicultural education carried in Turkey between 2005 and 2014, expressed that the publications made in this field centered upon students' attitude, knowledge, awareness and classroom environments. As a continuation of this study, Köşker & Erdoğan (2020) looked into the studies on multicultural education between 2014 and 2018 with content analysis. Their study concluded that the studies on multicultural education gradually increased and, while they showed similarities to those in the previous study, the subjects researched were enriched, and new studies were carried out on multicultural education practices and multicultural education tools.…”
Section: Multicultural Education In Social Studies Coursementioning
confidence: 99%
“…Although multicultural education is a type of education based on the dynamics of multiculturalism, it is not an education that is only provided to students who are not members of the dominant culture of the society and who are of different cultures, but it is a type of education that provides equal educational opportunities to all students (Acar Çiftçi & Aydın, 2014). Köşker & Erdoğan (2020) states that multicultural education helps students to develop positive attitudes towards individuals from different cultural groups, reduces their discriminatory attitudes, increases the level of tolerance between groups, and thus provides students with opportunities and experiences to get to know their own culture and other cultures. In societies where cultural differences such as ethnic origin, race, language, religion, gender, etc.…”
Section: Introductionmentioning
confidence: 99%